Institutions and Political Strategy in Post-Marxist Discourse Theory: A Reply to Pedro Rey-Araújo. Issue 1 (2nd January 2021) - Jacobs, Thomas
Abstract : This reply to Pedro Rey-Araújo's essay "Ernesto Laclau's Oblivion of Political Economy" appreciates the importance of Rey-Araújo's attempt to situate political strategy at the core of post-Marxist discourse theory (PDT) but finds several problems with the execution of this move. First, Rey-Araújo sets out to resolve PDT's so-called "institutional deficit" but overlooks the existence of a substantial literature tackling this issue. Second, Rey-Araújo's treatment divorces institutions from the hegemonic logics that play out within their confines. This ontological dualism negates the crucial insight that PDT brings to institutional research, notably that institutions are fundamentally discursive in nature and cannot be separated from the political processes that constitute them. Finally, this ontological dualism unduly limits the scope for strategic reflection through PDT. In postulating the inherently capitalist nature of the institutions within which hegemonic struggles play out, several potential political strategies are foreclosed.